INSTRUCTIONAL LEADERSHIP STRATEGIES OF SCHOOL PRINCIPALS IN ENHANCING LANGUAGE TEACHERS’ PERFORMANCE - Tataq Harjuna Piranggada; Muhammad Triyoso; Muhsinin; Sahdat; Ahmad Suriansyah; Ratna Purwanti (Esteem Journal of English Education Study Programme, 2025)
The instructional leadership at SDN Pelajau Baru plays a significant role in improving language teachers’ performance and the overall quality of language instruction through structured managerial strategies. This study highlights the implementation of various instructional leadership strategies, including the establishment of Professional Learning Communities (PLCs), data-driven supervision, and participatory leadership approaches. The findings reveal that effective instructional leadership in this school is supported by the principal’s and teachers’ professional competence, digital literacy, and emotional intelligence. Nonetheless, the study also identifies key challenges such as excessive administrative workload and limited time for instructional supervision. Strengthening the capacity of school principals through intensive training and integrating supervision practices into PLC forums are recommended to address these issues. Overall, the research underscores that consistent and well-executed instructional leadership has a positive impact on enhancing language teachers’ motivation, professionalism, and the quality of language teaching in primary education.